A method for preparing high-strength aluminum alloy for automobile structural parts
By using shell-like structures to enhance the composite of particles and modified basalt fibers with aluminum alloys in automotive structural parts, the problem of insufficient strength and toughness of aluminum alloy materials is solved, and the effects of high strength and high toughness are achieved.
Patent Information
- Application Number
- CN202410004268.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-01-03
AI Technical Summary
The existing aluminum alloy materials lack strength and toughness in automotive structural parts, making it difficult to meet performance requirements.
The shell-like structure is used to enhance the composite of particles and modified basalt fibers with aluminum alloy. By introducing shell powder into boron carbide as a weak interface layer, the toughness of the aluminum alloy is enhanced, and the impact force is dispersed by modified basalt fibers to improve fracture toughness.
The high strength and toughness of aluminum alloy materials are achieved, and a large amount of fracture energy can be consumed in the weak interface layer, thereby improving the impact resistance of the material.
Smart Images

Figure BDA0004646036430000051 
Figure BDA0004646036430000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy materials, and in particular to a method for preparing an aluminum alloy for high-strength automobile structural parts. Background Art
[0002] Aluminum is the most widely used nonferrous metal. It is an important functional and structural material for the development of the national economy and one of the most widely used and economical materials. At present, China is the world's largest producer, consumer and trader of primary aluminum. In recent decades, aluminum alloys for automotive structural parts have been increasingly widely used due to their advantages such as light weight and good strength. However, in the process of continuous development, the strength and toughness of ordinary aluminum alloys have been increasingly unable to meet the performance requirements of automotive structural parts. Therefore, how to improve the strength and toughness of automotive structural aluminum alloys is one of the important issues that need to be solved at present.
[0003] Most natural biomaterials have quite good physical and mechanical properties. The excellent properties and special functions of natural biomaterials may far exceed those of artificial materials with similar components and compositions. The reason is that natural biomaterials are optimized by nature at all scales from molecules to nanometers and micrometers, forming microstructures optimized in shape, scale and distribution. For example, shells in nature are a typical natural bioceramic composite material. After several centuries of selective evolution, shells have excellent mechanical properties of both strength and toughness. Studies have shown that although shells are composed of brittle inorganic calcium carbonate (accounting for 95% to 99%) and organic collagen (accounting for 1% to 5%), their fracture toughness can reach 3000 times that of ordinary pure calcium carbonate. The excellent mechanical properties of shells are attributed to the microstructure shape, size, distribution and combination relationship of the inorganic calcium carbonate and organic collagen inside them. Therefore, how to effectively utilize its properties and apply them to aluminum alloys for automotive structural parts is a problem that needs to be solved in this application. Summary of the invention
[0004] Technical problems to be solved: In view of the above technical problems, the purpose of the present invention is to provide a method for preparing high-strength aluminum alloy for automotive structural parts. After the shell-like structure reinforcing particles / modified basalt fibers are compounded with the aluminum alloy, shell powder is introduced into the boron carbide, and the shell powder is used as a weak interface layer, so that the cracks are repeatedly deflected in the weak interface layer, consuming a large amount of fracture energy, thereby obtaining high toughness of the aluminum alloy; modified basalt fibers are used to improve the toughness of the aluminum alloy. The modified basalt fibers are in the shape of a tube and have a higher energy absorption capacity. When the aluminum alloy is impacted, the modified basalt fibers can disperse the impact force and disperse the force to the shell-like structure reinforcing particles, thereby enhancing the fracture toughness of the aluminum alloy.
[0005] Technical solution: A high-strength aluminum alloy for automobile structural parts, comprising the following components, by weight percentage: 100 parts of aluminum alloy substrate, 10-19 parts of shell-like structure reinforcement particles and 2-5 parts of modified basalt fiber;
[0006] The aluminum alloy substrate composition comprises:
[0007] Si 5.12%
[0008] Zn 3.24%
[0009] Mg 2.25%
[0010] Fe 0.51%
[0011] Al Residue.
[0012] Furthermore, the particle size of the shell-like structure reinforcement particles is ≤30 μm.
[0013] Furthermore, the preparation method of the shell-like structure reinforced particles is as follows:
[0014] S1: Take 10 parts of shell powder and 20-30 parts of boron carbide powder, stir and soak them in 90-100 parts of ethanol for 1-2 hours;
[0015] S2: Filter, dry, add 40 parts of deionized water and 0.9-1 parts of dispersant, and perform primary ball milling at a speed of 500-600 rpm for 6 hours to form a suspension;
[0016] S3: adding 12-13 parts of acrylic acid copolymer and 1-1.5 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 300-400 rpm for 6 hours to obtain a slurry;
[0017] S4: performing vacuum degassing to obtain a casting slurry;
[0018] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0019] S6: After drying, a thin sheet is obtained, which is laminated and pressed and then debonded in a tubular debonding furnace;
[0020] S7: hot pressing and sintering for 1-2h in a hot pressing furnace at 2100-2200°C, 20-35MPa pressure and argon protection;
[0021] S8: After crushing, shell-like structure reinforced particles are obtained.
[0022] Furthermore, the dispersant includes polyethyleneimine and polyacrylic acid.
[0023] Furthermore, the specific process of the debinding is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and then naturally cooled to room temperature after keeping the temperature for 1 hour.
[0024] Furthermore, the aspect ratio of the modified basalt fiber is 1:(800-1200).
[0025] Furthermore, the preparation method of the modified basalt fiber is as follows: taking basalt fiber, pre-treating it with an acetone solution, etching it, and rinsing it to obtain the modified basalt fiber.
[0026] Furthermore, the reagent used for etching is sodium hydroxide solution or hydrochloric acid solution, and the mass volume ratio of the basalt fiber to the reagent is 1g:20ml.
[0027] The method for preparing the above-mentioned high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0028] Step 1: Soaking the shell-like structure reinforcement particles in an amino-type silane coupling agent solution for 1 hour to obtain amino-modified shell-like structure reinforcement particles;
[0029] Step 2: Disperse the modified basalt fiber in water, add the amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0030] Step 3: Filter and dry;
[0031] Step 4: Mix and melt with the aluminum alloy substrate, stir evenly, and then cool and solidify to obtain a high-strength aluminum alloy for automobile structural parts. Further, the amino-type silane coupling agent solution is a mixed solution of an amino-type silane coupling agent and a 90% ethanol solution in a volume ratio of 20:500; the amino-type silane coupling agent includes KH550, KH602, KH540 and KH792.
[0032] Beneficial effects:
[0033] 1. The present invention uses a shell-like structure reinforcing particle / modified basalt fiber composite as a reinforcement, and adopts a coupling method to connect or load the shell-like structure reinforcing particles and the modified basalt fiber, so that it has both high strength and high toughness.
[0034] 2. After the shell-like structure reinforcing particles / modified basalt fibers of the present invention are compounded with aluminum alloy, shell powder is introduced into boron carbide, and the shell powder is used as a weak interface layer, so that cracks are repeatedly deflected in the weak interface layer, consuming a large amount of fracture energy, thereby obtaining high toughness of the aluminum alloy.
[0035] 3. The present invention adopts modified basalt fiber to improve the toughness of aluminum alloy. The modified basalt fiber is in a cylindrical shape and has a higher energy absorption capacity. When the aluminum alloy is impacted, the modified basalt fiber can disperse the impact force and disperse the force to the shell structure reinforcement particles, thereby enhancing the fracture toughness of the aluminum alloy. DETAILED DESCRIPTION
[0036] The present invention proposes a method for preparing a high-strength aluminum alloy for automotive structural parts. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] All aluminum alloy substrates in the following examples have the following composition: Si 5.12%, Zn 3.24%, Mg 2.25%, Fe 0.51% and the balance Al.
[0038] Example 1
[0039] The preparation method of the shell-like structure reinforced particles is as follows:
[0040] S1: Take 10 parts of shell powder and 20 parts of boron carbide powder, stir and soak in 90 parts of ethanol for 1 hour;
[0041] S2: Filter, dry, add 40 parts of deionized water and 0.9 parts of polyethyleneimine, and perform primary ball milling at a speed of 500 rpm for 6 hours to form a suspension;
[0042] S3: adding 12 parts of acrylic copolymer and 1 part of polyethylene glycol, and performing secondary ball milling at a rotation speed of 300 rpm for 6 hours to obtain a slurry; S4: performing vacuum degassing to obtain a casting slurry;
[0043] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0044] S6: After drying, the thin slices are obtained, and after lamination and pressing, the binder is removed in a tubular binder removal furnace; the specific process of binder removal is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and the temperature is kept for 1 hour and then naturally cooled to room temperature;
[0045] S7: hot pressing sintering for 2 h in a hot pressing furnace at 2100°C, 20 MPa pressure and argon protection;
[0046] S8: After crushing, shell-like structure reinforced particles are obtained.
[0047] Example 2
[0048] The preparation method of the shell-like structure reinforced particles is as follows:
[0049] S1: Take 10 parts of shell powder and 25 parts of boron carbide powder, stir and soak in 95 parts of ethanol for 1-2 hours;
[0050] S2: Filter, dry, add 40 parts of deionized water and 0.95 parts of polyethyleneimine, and perform primary ball milling at 550 rpm for 6 hours to form a suspension;
[0051] S3: adding 12 parts of acrylic acid copolymer and 1.2 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 350 rpm for 6 hours to obtain a slurry;
[0052] S4: performing vacuum degassing to obtain a casting slurry;
[0053] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0054] S6: After drying, the thin slices are obtained, and after lamination and pressing, the binder is removed in a tubular binder removal furnace; the specific process of binder removal is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and the temperature is kept for 1 hour and then naturally cooled to room temperature;
[0055] S7: hot pressing sintering for 2 h in a hot pressing furnace at 2150°C, 25 MPa pressure and argon protection;
[0056] S8: After crushing, shell-like structure reinforced particles are obtained.
[0057] Example 3
[0058] The preparation method of the shell-like structure reinforced particles is as follows:
[0059] S1: Take 10 parts of shell powder and 25 parts of boron carbide powder, stir and soak in 95 parts of ethanol for 1.5 hours;
[0060] S2: Filter, dry, add 40 parts of deionized water and 0.95 parts of polyethyleneimine, and perform primary ball milling at 550 rpm for 6 hours to form a suspension;
[0061] S3: adding 12.5 parts of acrylic acid copolymer and 1.3 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 350 rpm for 6 hours to obtain a slurry;
[0062] S4: performing vacuum degassing to obtain a casting slurry;
[0063] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0064] S6: After drying, the thin slices are obtained, and after lamination and pressing, the binder is removed in a tubular binder removal furnace; the specific process of binder removal is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and the temperature is kept for 1 hour and then naturally cooled to room temperature;
[0065] S7: hot pressing sintering for 1.5 h in a hot pressing furnace at 2150°C, 30 MPa pressure, and argon protection;
[0066] S8: After crushing, shell-like structure reinforced particles are obtained.
[0067] Example 4
[0068] The preparation method of the shell-like structure reinforced particles is as follows:
[0069] S1: Take 10 parts of shell powder and 25 parts of boron carbide powder, stir and soak in 95 parts of ethanol for 1.5 hours;
[0070] S2: Filter, dry, add 40 parts of deionized water and 0.95 parts of polyethyleneimine, and perform primary ball milling at 550 rpm for 6 hours to form a suspension;
[0071] S3: adding 13 parts of acrylic acid copolymer and 1.4 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 350 rpm for 6 hours to obtain a slurry;
[0072] S4: performing vacuum degassing to obtain a casting slurry;
[0073] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0074] S6: After drying, the thin slices are obtained, and after lamination and pressing, the binder is removed in a tubular binder removal furnace; the specific process of binder removal is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and the temperature is kept for 1 hour and then naturally cooled to room temperature;
[0075] S7: hot pressing sintering for 1 h in a hot pressing furnace at 2150°C, 30 MPa pressure and argon protection;
[0076] S8: After crushing, shell-like structure reinforced particles are obtained.
[0077] Example 5
[0078] The preparation method of the shell-like structure reinforced particles is as follows:
[0079] S1: Take 10 parts of shell powder and 30 parts of boron carbide powder, stir and soak them in 100 parts of ethanol for 2 hours;
[0080] S2: Filter, dry, add 40 parts of deionized water and 1 part of polyethyleneimine, and perform primary ball milling at 600 rpm for 6 hours to form a suspension;
[0081] S3: adding 13 parts of acrylic acid copolymer and 1.5 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 400 rpm for 6 h to obtain a slurry;
[0082] S4: performing vacuum degassing to obtain a casting slurry;
[0083] S5: using a mold to press a sheet green body with a thickness of 100 μm;
[0084] S6: After drying, the thin slices are obtained, and after lamination and pressing, the binder is removed in a tubular binder removal furnace; the specific process of binder removal is: firstly, the temperature is increased to 100°C at 1°C / min, then the temperature is increased to 600°C at 0.5°C / min, and finally the temperature is increased to 800°C at 1°C, and the temperature is kept for 1 hour and then naturally cooled to room temperature;
[0085] S7: hot pressing sintering in a hot pressing furnace at 2200°C, 35MPa pressure, and argon protection for 1h;
[0086] S8: After crushing, shell-like structure reinforced particles are obtained.
[0087] The mechanical properties of the shell-like structure reinforced particles before crushing were tested, and the results are shown in Table 1:
[0088] Table 1
[0089]
[0090]
[0091] It can be seen from Table 1 that the mechanical properties of Example 4 are the best, so the shell structure reinforced particles prepared in Example 4 were selected for subsequent tests.
[0092] Example 6
[0093] The preparation method of modified basalt fiber is as follows: take basalt fiber, pre-treat it with acetone solution and then etch it, the etching reagent used is hydrochloric acid solution, the mass volume ratio of basalt fiber to hydrochloric acid solution is 1g:20ml, and the modified basalt fiber is obtained after rinsing.
[0094] Example 7
[0095] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0096] Step 1: immerse 10 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0097] Step 2: Disperse 4 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0098] Step 3: Filter and dry;
[0099] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0100] Example 8
[0101] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0102] Step 1: immerse 12 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0103] Step 2: Disperse 4 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0104] Step 3: Filter and dry;
[0105] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0106] Example 9
[0107] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0108] Step 1: immerse 15 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0109] Step 2: Disperse 4 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0110] Step 3: Filter and dry;
[0111] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0112] Example 10
[0113] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0114] Step 1: immerse 17 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0115] Step 2: Disperse 4 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0116] Step 3: Filter and dry;
[0117] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0118] Embodiment 11
[0119] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0120] Step 1: immerse 19 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0121] Step 2: Disperse 4 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0122] Step 3: Filter and dry;
[0123] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0124] Example 12
[0125] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0126] Step 1: immerse 17 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0127] Step 2: Disperse 2 parts of modified basalt fibers with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0128] Step 3: Filter and dry;
[0129] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0130] Embodiment 13
[0131] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0132] Step 1: immerse 17 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0133] Step 2: Disperse 5 parts of modified basalt fiber with an aspect ratio of 1:(800-1200) in water, add amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution;
[0134] Step 3: Filter and dry;
[0135] Step 4: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0136] Comparative Example 1
[0137] The difference between this comparative example and Example 10 is that no shell-like structure reinforcing particles are added, specifically:
[0138] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0139] Step 1: Disperse 4 parts of modified basalt fiber with an aspect ratio of 1:(800-1200) in water;
[0140] Step 2: Filter and dry;
[0141] Step 3: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0142] Comparative Example 2
[0143] The difference between this comparative example and Example 10 is that no modified basalt fiber is added, specifically:
[0144] A method for preparing a high-strength aluminum alloy for automobile structural parts comprises the following steps:
[0145] Step 1: immerse 17 portions of shell-like structure reinforced particles with a particle size of ≤30 μm prepared in Example 4 in a silane coupling agent KH602 solution for 1 hour to obtain amino-modified shell-like structure reinforced particles; the silane coupling agent KH602 solution is a mixture of silane coupling agent KH602 and 90% ethanol solution in a volume ratio of 20:500;
[0146] Step 2: Filter and dry;
[0147] Step 3: Mix and melt with 100 parts of aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
[0148] The mechanical properties of each embodiment were tested using a universal testing machine.
[0149] Table 2
[0150] Yield strength (MPa) Tensile strength(MPa) Hardness HV Example 7 493.6 620.6 1861 Example 8 498.5 623.8 1870 Example 9 499.9 627.1 1876 Example 10 501.2 630.0 1889 Embodiment 11 501.5 630.1 1890 Example 12 495.3 623.4 1885 Example 13 501.7 629.9 1888 Comparative Example 1 478.1 601.8 1684 Comparative Example 2 490.6 620.2 1870
Claims
1. A high-strength aluminum alloy for automotive structural parts, characterized in that: The composition comprises the following components by weight percentage: 100 parts of aluminum alloy substrate, 10-19 parts of shell-like structure reinforcement particles and 2-5 parts of modified basalt fiber; The aluminum alloy substrate composition comprises: Si 5.12% Zn 3.24% Mg 2.25% Fe 0.51% Al remainder; The preparation method of the shell-like structure reinforced particles is as follows: S1: Take 10 parts of shell powder and 20-30 parts of boron carbide powder, stir and soak them in 90-100 parts of ethanol for 1-2 hours; S2: Filter, dry, add 40 parts of deionized water and 0.9-1 parts of dispersant, and perform primary ball milling at a speed of 500-600 rpm for 6 hours to form a suspension; S3: adding 12-13 parts of acrylic acid copolymer and 1-1.5 parts of polyethylene glycol, and performing secondary ball milling at a rotation speed of 300-400 rpm for 6 hours to obtain a slurry; S4: performing vacuum degassing to obtain a casting slurry; S5: using a mold to press a sheet green body with a thickness of 100 μm; S6: After drying, a thin sheet is obtained, which is laminated and pressed and then debonded in a tubular debonding furnace; S7: hot pressing and sintering for 1-2h in a hot pressing furnace at 2100-2200°C, 20-35MPa pressure and argon protection; S8: After crushing, shell-like structure reinforced particles are obtained.
2. The high-strength aluminum alloy for automobile structural parts according to claim 1, characterized in that: The particle size of the shell-like structure reinforcement particles is ≤30 μm.
3. The high-strength aluminum alloy for automobile structural parts according to claim 1, characterized in that: The dispersant includes polyethyleneimine and polyacrylic acid.
4. The high-strength aluminum alloy for automobile structural parts according to claim 1, characterized in that: The specific process of debinding is: firstly, heating to 100°C at 1°C / min, then heating to 600°C at 0.5°C / min, and finally heating to 800°C at 1°C, keeping the temperature for 1 hour, and then naturally cooling to room temperature.
5. The high-strength aluminum alloy for automobile structural parts according to claim 1, characterized in that: The aspect ratio of the modified basalt fiber is 1:(800-1200).
6. The high-strength aluminum alloy for automobile structural parts according to claim 1, characterized in that: The preparation method of the modified basalt fiber is as follows: basalt fiber is taken, pre-treated with an acetone solution, then etched, and rinsed to obtain the modified basalt fiber.
7. The high-strength aluminum alloy for automobile structural parts according to claim 6, characterized in that: The reagent used for etching is sodium hydroxide solution or hydrochloric acid solution, and the mass volume ratio of the basalt fiber to the reagent is 1g:20ml.
8. A method for preparing a high-strength aluminum alloy for automobile structural parts according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Soaking the shell-like structure reinforcement particles in an amino-type silane coupling agent solution for 1 hour to obtain amino-modified shell-like structure reinforcement particles; Step 2: Disperse the modified basalt fiber in water, add the amino-modified shell-like structure reinforcement particles and stir to obtain a mixed solution; Step 3: Filter and dry; Step 4: Mix and melt with the aluminum alloy substrate, stir evenly and cool and solidify to obtain high-strength aluminum alloy for automobile structural parts.
9. The method for preparing a high-strength aluminum alloy for automobile structural parts according to claim 8, characterized in that: The amino-type silane coupling agent solution is a mixed solution of an amino-type silane coupling agent and an ethanol solution with a concentration of 90% in a volume ratio of 20:500; the amino-type silane coupling agent includes KH550, KH602, KH540 and KH792.
Citation Information
Patent Citations
B4C / Al shell-imitated gradient armor and preparation method thereof
CN115365504A
Method of manufacturing aluminium-based composite material
WO2006134405A1